2020
DOI: 10.3389/fonc.2020.01436
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein C1 (APOC1): A Novel Diagnostic and Prognostic Biomarker for Clear Cell Renal Cell Carcinoma

Abstract: Background: Apolipoprotein C1 (APOC1) has been proved to play a critical role in gastric, breast, lung, and pancreatic cancer. However, the relationship between APOC1 and urinary tumors remains unclear. This study aimed to assess the diagnostic and prognostic value of APOC1 in urinary tumors. Methods: We performed a pan analysis of APOC1 mRNA expression in urinary cancer using the Gene Expression Profiling Interactive Analysis (GEPIA) database. To further investigate the prognostic value of APOC1 expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…A PubMed [64] search returns thousands (5579 on 11 October 2020) of gene expression studies on ccRCC (among the most recent [65][66][67]), most of them performed on large populations of healthy and cancer subjects. Thus, what novel findings can another study on a single case bring?…”
Section: Discussionmentioning
confidence: 99%
“…A PubMed [64] search returns thousands (5579 on 11 October 2020) of gene expression studies on ccRCC (among the most recent [65][66][67]), most of them performed on large populations of healthy and cancer subjects. Thus, what novel findings can another study on a single case bring?…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous (1,459 listed in PubMed [62]) studies using microarray data to identify altered gene expression profiles and biomarkers in ccRCC nodules with respect to normal counterparts (among the most recent [63][64][65]). One may ask: How are these findings a departure from other studies?…”
Section: Discussionmentioning
confidence: 99%
“…Cox regression analysis suggested that APOC1 expression remained as an independent prognostic factor for OS of ccRCC patients. A recent study by Cui et al revealed that high expression of APOC1 was correlated with shorter overall survival ( P =0.022) and progression-free survival ( P =0.007), and APOC1 may serve as a novel diagnostic biomarker for ccRCC [ 16 ]. Besides ccRCC, high expression of APOC1 has been found in CRC, and APOC1 overexpression contributed to the poor prognosis of CRC patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study speculated that APOC1 may act as a tumor promoter by regulating cholesterol metabolism, and APOC1 might play a key role in the tumorigenesis and progression of ccRCC [ 16 ]. A study by Li et al indicated that APOC1 acts as a novel pro-metastatic factor, which facilitated the activation of STAT3 and enhanced the metastasis of ccRCC cells [ 17 ].…”
Section: Discussionmentioning
confidence: 99%